Formative Assessment in the Merdeka Curriculum English Textbook entitled English for Nusantara - Jajang Nooralam; Zulfa Sakhiyya (English Education Journal, 2022)
Using formative assessment to analyze tasks in the textbook is uncommonly used. Textbooks as the primary resources should follow the latest curriculum version in teaching-learning processes. This study aimed at investigating the implementation of formative assessment on speaking and writing activities in the "English for Nusantara" textbook. Qualitative research was used as the approach to collect and analyze the research. Types of speaking and writing assessment in the textbook were analyzed using assessing speaking skills by Brown (2003) and typical formative activity and criteria by Irons (2008). The result showed that the majority of formative assessment tasks used in this textbook are discussions and conversations (interactive speaking), one each type of oral presentation (extensive speaking), and picture-cued tasks (intensive/extensive speaking). In addition to that, the commonly used writing tasks in the textbook are paragraph construction tasks (responsive and extensive writing), short-answer and sentence completion tasks (intensive writing), and guided question and answer. Furthermore, typical formative activities found in the textbook are diagnostic tests, practical exercises, student demonstrations, group discussion/work, student presentations, checklists, and self-assessments. Finally, the findings of this study may provide scientific information about types of formative assessment in the textbook to support teacher practices in the implementation of formative assessment. Finally, future studies are needed to continue this research by using a curriculum guide with varying levels in order to obtain more information regarding the formative assessment.